Disclosure of non-current tangible assets information in private sector entities financial statements: The case of Lithuania - Rasa Kanapickiene; Greta Keliuotyte-Staniuleniene; Deimante Teresiene (Economies, 2021)
The research aims to examine and evaluate the accounting information disclosure (AID) quality of the non-current tangible assets in the annual financial statements of private sector entities of Lithuania and identify characteristics of these enterprises that have an impact on the AID quality. The research model of the AID quality in the financial statements is created. Based on the national accounting standards' legal requirements, the original checklists were structured, and the disclosure quality indexes (DQIs) allowing evaluation of AID (both mandatory and voluntary) quality were formed. The empirical results show that Lithuanian enterprises' AID quality was sufficient and average during the investigation period. The significant AID quality change was not observed during the short term (2007-2008), i.e., when Lithuania was going through a significant change in the economy, where the rapid growth was followed by the financial crisis. In addition, it was investigated whether significant changes were observed during the long term (2007-2016) when Lithuania was transforming from a developing to a developed country. The results show that during this period the disclosure of mandatory (for all enterprises) and voluntary information did not change significantly, while additional (for large and medium) AID quality increased. Multiple panel regression analysis showed that the enterprise's characteristics (such as its size, debt-paying capacity, indebtedness, tangible assets, and profitability) appeared to have a statistically significant effect on the AID quality. The research findings could contribute to helping shareholders, potential investors or creditors, financial analysts, and other stakeholders when making decisions in regard to the evaluation of the AID quality as well as helping regulators to increase standards for information transparency and comparability.
Keywords: H83; M41; M48; 330; accounting information disclosure quality; disclosure quality index; financial reporting; non-current tangible assets; private sector